2002
DOI: 10.1124/jpet.300.3.1085
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Corticotropin-Releasing Factor Neuronal Systems and Hypothalamic-Pituitary-Adrenal Axis Activity by Stress and Chronic Antidepressant Treatment

Abstract: In a series of experiments, we tested the hypothesis that chronic antidepressant drug administration reduces the synaptic availability of corticotropin-releasing factor (CRF) through one or more effects on CRF gene expression or peptide synthesis. We also determined whether effects of acute or chronic stress on CRF gene expression or peptide concentration are influenced by antidepressant drug treatment. Four-week treatment with venlafaxine, a dual serotonin (5-HT)/norepinephrine (NE) reuptake inhibitor, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 31 publications
2
55
1
Order By: Relevance
“…As CRH and AVP gene expressions are under glucocorticoid control, it has been hypothesized that corticosteroid signalling is impaired in major depression and may be improved via antidepressant drug treatment (Holsboer and Barden, 1996;Ma and Aguilera, 1999). In contrast to antidepressant-induced decreases in CRH, although suggested by in vitro studies, similar changes have not been shown for AVP or its receptors in vivo (Brady et al, 1991;Altemus et al, 1992;Butterweck et al, 2001;Stout et al, 2002). Thus, an appropriate animal model that reflects both significant psychopathological and neuroendocrine features of human depression with face, predictive and construct validity should be used to obtain predictions about the clinical condition in human depression (Geyer and Markou, 1995).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…As CRH and AVP gene expressions are under glucocorticoid control, it has been hypothesized that corticosteroid signalling is impaired in major depression and may be improved via antidepressant drug treatment (Holsboer and Barden, 1996;Ma and Aguilera, 1999). In contrast to antidepressant-induced decreases in CRH, although suggested by in vitro studies, similar changes have not been shown for AVP or its receptors in vivo (Brady et al, 1991;Altemus et al, 1992;Butterweck et al, 2001;Stout et al, 2002). Thus, an appropriate animal model that reflects both significant psychopathological and neuroendocrine features of human depression with face, predictive and construct validity should be used to obtain predictions about the clinical condition in human depression (Geyer and Markou, 1995).…”
Section: Introductionmentioning
confidence: 78%
“…Correspondingly, basal and stress-induced plasma ACTH and corticosterone levels were comparable in the paroxetine-treated and control HAB and LAB rats during week 9 of paroxetine treatment. Similarly, in other studies, long-term treatment with the SRIs fluoxetine and paroxetine did not prevent adequate activation of the HPA system in response to severe stressors such as FS, immobilization or footshocks (Zhang et al, 2000;Connor et al, 2000;Stout et al, 2002). In contrast, we could show that after DEX pretreatment, basal ACTH levels at the onset of the activity The density of silver grains per cell within the magnocellular part of the PVN was significantly higher in the vehicle-treated HAB (HAB-V) rats than in the LAB rats and decreased after paroxetine treatment in HAB rats (HAB-P) (n ¼ 6 per group).…”
Section: Long-term Paroxetine Normalizes the Aberrant Outcome Of The mentioning
confidence: 99%
“…Acute stress causes upregulation of CRF in amygdala (Stout et al, 2002). Stimulation of amygdalar CRF receptors, and consequent increase in amygdalar metabolic activity, results in increased anxiety-like and decreased pro-social behaviors (Strome et al, 2002;DeVries et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ability of glucocorticoid hormones to exert negative feedback on HPA axis activity appears to be deficient in depression, resulting in a feed-forward hyperactivation of this system (Parker et al, 2003;Holsboer, 2000). This enhanced output of the HPA axis appears functionally relevant to depression, as long-term antidepressant treatment attenuates this phenomenon in humans (De Bellis et al, 1993;Pariante et al, 2004;Greden et al, 1983;Michelson et al, 1997), and suppresses stress-induced activation of the HPA axis in other species (Reul et al, 1993;Connor et al, 2000;Holsboer and Barden, 1996;de Medeiros et al, 2005;Butterweck et al, 2001;Stout et al, 2002). The ability of antidepressants to suppress HPA axis hyperactivity has been shown to be coupled to their clinical efficacy (Appelhof et al, 2006;Young et al, 2004).…”
Section: Introductionmentioning
confidence: 99%